2017
DOI: 10.1038/s41467-017-02322-5
|View full text |Cite|
|
Sign up to set email alerts
|

Excitotoxic inactivation of constitutive oxidative stress detoxification pathway in neurons can be rescued by PKD1

Abstract: Excitotoxicity, a critical process in neurodegeneration, induces oxidative stress and neuronal death through mechanisms largely unknown. Since oxidative stress activates protein kinase D1 (PKD1) in tumor cells, we investigated the effect of excitotoxicity on neuronal PKD1 activity. Unexpectedly, we find that excitotoxicity provokes an early inactivation of PKD1 through a dephosphorylation-dependent mechanism mediated by protein phosphatase-1 (PP1) and dual specificity phosphatase-1 (DUSP1). This step turns off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 61 publications
0
19
0
3
Order By: Relevance
“…This constitutive activity is beneficial for neuronal survival, as well as for learning and memory, and, thus, might favor the transcription of genes involved in these processes. However, NF-κB activation favored cell death or damage in pathophysiological models that involve NMDA receptor overactivation 56,57,58 while it resulted neuroprotective in cortical neurons both in vitro and in vivo 21 . It is unknown how an excitotoxic insult might switch NF-B activity to promote the expression of deleterious or pro-inflammatory proteins 59 .…”
Section: Nf-κb and Enos-dependent No Production In The Cerebral Cortexmentioning
confidence: 99%
“…This constitutive activity is beneficial for neuronal survival, as well as for learning and memory, and, thus, might favor the transcription of genes involved in these processes. However, NF-κB activation favored cell death or damage in pathophysiological models that involve NMDA receptor overactivation 56,57,58 while it resulted neuroprotective in cortical neurons both in vitro and in vivo 21 . It is unknown how an excitotoxic insult might switch NF-B activity to promote the expression of deleterious or pro-inflammatory proteins 59 .…”
Section: Nf-κb and Enos-dependent No Production In The Cerebral Cortexmentioning
confidence: 99%
“…While PKD-induced NF- κ B activity in transformed cells contributes to tumor development, this pathway has recently also been shown to contribute to the physiological steady-state survival of neuronal cells. Indeed, in these cells, the PKD-NF- κ B-SOD2 axis is constitutively active and protects against oxidative damage [ 88 ]. In a model of excitotoxic neurodegeneration, which results in endoplasmic reticulum stress and mitochondrial dysfunction, high levels of ROS, and oxidative stress damage, the authors showed that PKD1 is rapidly deactivated after a short burst of activity, resulting in the loss of NF- κ B signaling and impeding neuronal survival [ 88 ].…”
Section: Protein Kinase Dmentioning
confidence: 99%
“…Indeed, in these cells, the PKD-NF- κ B-SOD2 axis is constitutively active and protects against oxidative damage [ 88 ]. In a model of excitotoxic neurodegeneration, which results in endoplasmic reticulum stress and mitochondrial dysfunction, high levels of ROS, and oxidative stress damage, the authors showed that PKD1 is rapidly deactivated after a short burst of activity, resulting in the loss of NF- κ B signaling and impeding neuronal survival [ 88 ]. These findings were further substantiated in vivo using patient samples and an ischemic mouse model [ 88 ].…”
Section: Protein Kinase Dmentioning
confidence: 99%
See 2 more Smart Citations